Half-Time and High-Speed Running in the Second Half of Soccer - Mugglestone, C.; Morris, J. G.; Saunders, B.; Sunderland, C. (International Journal of Sports Medicine, 2013)
This study investigated if the quantity of high-speed running (movements >15 km.h − 1) completed in the first 15 min of competitive football matches differed from that completed in the corresponding 15 min of the second half. 20 semi-professional soccer players (age 21.2±3.6 years, body mass 76.4±3.8 kg, height 1.89±0.05 m) participated in the study. 50 competitive soccer matches and 192 data files were analysed (4±2 files per match) using Global Positioning Satellite technology. Data were analysed using 2-way repeated measures ANOVA and Pearson correlations. No differences were found between the first 15 min of each half for the distance completed at high-speed (>15 km.h − 1) or sprinting (>21 km.h − 1), or in the number of sprints undertaken (p>0.05). However, total distance covered was shorter (1st half vs. 2nd half: 1 746±220 vs. 1 644±224 m; p<0.001) and mean speed lower (1st half vs. 2nd half: 7.0±0.9 vs. 6.6±0.9 km.h − 1; p<0.001) in the first 15 min of the second half compared to the first. The correlations between the duration of the half-time interval and the difference in the high-speed running or sprinting between first and second halves (0–15 min) were very small (r=0.08 [p=0.25] and r=0.04 [p=0.61] respectively). Therefore, this study did not find any difference between the amount of high-speed running and sprinting completed by semi-professional soccer players when the first 15 min of the first and second half of competitive matches were compared The maintenance of high-speed running and sprinting, as total distance and mean speed declined, may be a function of the pacing strategies adopted by players in competitive matches.
Keywords: intermittent exercise; football; GPS; activity profiles